BERLAKUNYA KESETARAAN HAM, GENDER, DAN PEMBERDAYAAN PEREMPUAN BERDASARKAN PERSPEKTIF HUKUM INTERNASIONAL - Putu Tya Diliana; Ni Putu Rai Yuliartini (Jurnal Komunikasi Hukum, 2022)
This study aims to find out and also examine the equality of human rights. Gender and women's empowerment in the perspective of International Law, as well as reviewing solutions in cases of gender equality, human rights, and women's empowerment which will be discussed sequentially. The type of research used by the author in this study is normative legal research, a research method which in this case combines elements of normative law which is then supported by additional data or empirical elements. and case approach. This writing uses materials in doing writing with primary, secondary and tertiary legal materials which can show that this research is based on international law in general. A legal and normative concept which states that humans have rights that are very inherent in themselves because they are human beings who have full rights and these rights apply anytime and anywhere, differences that often occur make humans lose their rights such as inequality. Gander, which makes humans different from other humans, occurs very often, giving rise to the feeling that differences are a mistake. The progress achieved by a woman and the achievement of equality between women and men is one of the issues of human rights and a necessary condition for the welfare of society.